Butterfly‐Shaped Pentanuclear Dysprosium Single‐Molecule Magnets. Issue 39 (9th August 2013) - Tian, Haiquan; Zhao, Lang; Lin, Haifeng; Tang, Jinkui; Li, Guangshe
Abstract Two new "butterfly‐shaped" pentanuclear dysprosium(III) clusters, [Dy5(μ3‐OH)3(opch)6(H2O)3]⋅3 MeOH⋅ 9 H2O (1) and [Dy5(μ3‐OH)3(Hopch)2(opch)4(MeOH)(H2O)2]⋅(ClO4)2⋅ 6 MeOH⋅4 H2O (2), which were based on the heterodonor‐chelating ligand o‐vanillin pyrazine acylhydrazone (H2opch), have been successfully synthesized by applying different reaction conditions. Single‐crystal X‐ray diffraction analysis revealed that the butterfly‐shaped cores in both compounds were comparable. However, their magnetic properties were drastically different. Indeed, compound 1 showed dual slow‐relaxation processes with a transition between them that corresponded to energy gaps (Δ) of 8.1 and 37.9 K and pre‐exponential factors (τ0) of 1.7×10−5 and 9.7×10−8 s for the low‐ and high‐temperature domains, respectively, whilst only a single relaxation process was noted for compound 2 (Δ=197 K, τ0=3.2×10−9 s). These significant disparities are most likely due to the versatile coordination of the H2opch ligands with particular keto–enol tautomerism, which alters the strength of the local crystal field and, hence, the nature or direction of the easy axes of anisotropic dysprosium ions.